(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Klebsiella pneumoniae (K. pneumoniae) is an important pathogen in hospital and community-acquired urinary tract infections (HAUTI and CAUTI). It is showing a high resistance towards many antibiotics Objective: This study aims to estimate the percentage of K. pneumoniae in HAUTIs and CAUTIs, antibiotic resistance, extended spectrum bata lactamase (ESBL), and detect the beta lactamase K. pneumoniae carbapenemases (bla KPC) resistance gene and presence of mutation in this gene. Methods: A total of 200 urine samples were collected randomly; K. pneumoniae was cultured and isolated on MacConkey agar, antibiotic sensitivity testing and ESBL detection were performed by Vitek 2 system, then DNA was extracted, polymerase chain reaction and sequencing for KPC gene were done. Results: There was 7% (14 isolates) of K. pneumoniae (50%) HAUTI and (50%) CAUTI. ESBL was positive in 3 isolates (21.43%). Percentage of positive bla KPC gene was 42.8%. KPC gene sequencing showed high rate of mutation in positive isolates reaching to 50 different nucleotides. Conclusion: This work has increased the knowledge on K. pneumoniae causing HAUTI and CAUTI in Iraqi patients. Keywords: Klebsiella pneumoniae, hospital acquired urinary tract infection, community acquired urinary tract infection, ESBL, bla KPC gene. Citation: Nasser HH, Abdulrahman TR, Malik AS. Klebsiella pneumoniae in hospital acquired and community acquired urinary tract infections in an Iraqi cohort: Frequency, antibiotic susceptibility and the percentage of bla KPC resistance gene. Iraqi JMS. 2022; 20(1): 121-131. doi: 10.22578/IJMS.20.1.16